Efficiency of Closed Hemorrhoidectomy in the Treatment of Third-Degree Hemorrhoids - Muhammad Salman, Ibad Ur Rahman, Hafiza Kiran Saleem Butt, Ali Gohar Khan, Maria Shaikh, Farah Shah (Pakistan Journal of Medical & Health Sciences, 2023)
One of the most common surgical condition is hemorrhoids and estimated that one-fourth of all adults are affected. Four-grade hemorrhoids are resistant to non-surgical treatment and typically needed surgical intervention. Aim: The current study’s goal was to evaluate the effectiveness of closed hemorrhoidectomy for the treatment of third-degree haemorrhoids. Methods: Following approval from the hospital’s ethical and research committee, this case series study was held in the surgical department of Lady Reading Hospital, Peshawar from July 2021 to July 2022. The study included 100 patients in total with third-degree haemorrhoids of both genders. Patients were subjected to a proctoscopic examination following a digital rectal examination for diagnosis and closed hemorrhoidectomy was performed in appropriate patients. To assess the effectiveness of the procedure, these patients were followed up with one week after surgery for post-operative pain. The 10-point Visual Analogue Score (VAS), with 0 exhibiting no pain and 10 the most intense agony, was used to measure post-operative pain. The gender, age and post-operative pain parameters were documented in a proforma. SPSS version 22.0 was used for data entry and analysis. Results: The study included 100 individuals who underwent closed hemorrhoidectomy. The patients’ ages ranged from 20 to 65 years, with 42.58 years of mean age and 12.18 of S.D. 82 patients (82%) done with successful closed hemorrhoidectomy and exhibit good outcome in terms of postoperative pain. Conclusion: In patients with third-degree haemorrhoids, closed hemorrhoidectomy was helpful in terms of postoperative pain. Keywords: Hemorrhoids, Hemorrhoidectomy, Efficacy